Jasa Event Organizer Pendidikan Nonformal sebagai Konsep Usaha Baru bagi Wirausahawan Muda dalam Pendidikan Masyarakat - Alim Harun Pamungkas (RC-INSTITUT, 2020)
This article will illustrate the important aspects needed in managing an entrepreneurial service in the field of event organizers (EO). These aspects include business opportunities, the type, and type of business, as well as the needs and readiness in running an EO business. Service businesses or EO services can be understood as services about handling or managing an event that is done professionally, regularly, and planned starting from the preparation, implementation, and post-event. As a business that has economic benefits, EO is understood as a commercial service provided by a company to manage an event as a whole professionally.